(untitled) (La U Investiga, 2017)
Chronic obstructive pulmonary disease is characterized by airflow limitation that is not fully reversible. Generally obstruction evolves progressively and is associated with an abnormal inflammatory response of the lung to toxic particles or gases. An acute exacerbation induced by infection is a complication that can threaten patient’s life. This case report reviews a 68 year old woman with known chronic obstructive pulmonary disease. Exposed to a bacterial infection the disease of the patient aggravates and leads to an admission at intensive care unit and complex treatment. The following describes the arrival at intensive care unit, diagnostic procedures, therapy, recuperation and outcome of the patient. Objective of the case report is to analyze current therapy strategies, like for example from the “Global Initiative for Chronic Obstructive Lung Disease (GOLD)”, compared to former standard treatment regimens and emphasize the importance of smoking cessation in chronic obstructive pulmonary disease treatment.